The Effect of Learning Model and Creative Thinking Ability on Students’ Recount Writing Skill - Anggaira, Aria Septi; Rafli, Zainal (IJLECR (International Journal of Language Education and Cultural Review), 2016)
The aim of the study is to find out the effect of learning model and creative thinking ability on students’ recount writing skill. It was an experimental study with 2x2 factorial design and analysed using two-factor ANOVA at 0.05 significance level. The sample was 32 students and divided into two groups, namely experiment and control. The data were collected using recount writing test in English and creative thinking ability test. The research finding showed: (1) the students’ recount writing skill taught by project-based learning model was higher than by genre-based learning model, (2) there was interaction between learning model and creative thinking ability on students’ recount writing skill, (3) the students’ recount writing skill with high creative thinking ability taught by project-based learning model was higher than those by genre-based learning model, and (4) the students’ recount writing skill with low creative thinking ability taught by project-based learning model was lower than those by genre-based learning model.